The Role of Trace elements in Multiple Sclerosis. - Thamer, Ammar A.; Mohammed, Najeeb H.; Ibrahim, Akram M. (Journal of the Faculty of Medicine Baghdad, 2014)
Fac Med Baghdad 2014; Vol.56, No.2 Received: Feb., 2014 Accepted April. 2014 Background: Multiple sclerosis (MS) is a chronic, demyelinating disease of the central nervous system (CNS) affecting young adults and is considered as the leading cause of non traumatic neurological disability of young adults (1). The pathogenesis of MS is still incompletely understood. Deviation of immune responses in a genetically susceptible patient plays a central role in its pathogenesis (2). Electrophysiological, spinal tap and Radiological tools are important laboratory investigations that have added so much to the clinical diagnosis and for the classification of MS (3 and 4). Objectives: The aims of the study is to estimate and evaluate the oxidative status indirectly through the serum levels of copper, zinc, zinc/copper ratio and magnesium in patients with MS, in addition to their relation with patients` degree of disability. Patients and Methods: 112 patients with multiple sclerosis and 50 subjects without any neurological or psychiatric diseases as control group were recruited in this study. The cases were collected from Baghdad teaching hospital, MS center, Baghdad, Iraq at the period from May 2012 to April 2013, and studied at the toxicology center in Al-Shaheed Ghazi Al-Hareri Hospital in the Medical city. All patients and control groups were tested for serum level of copper, zinc and magnesium. Results: The present study showed that serum level of copper was significantly higher in patients than in control, while the serum level of zinc, zinc/copper ratio and magnesium, were significantly lower in patients group than the control group. Also there was a positive linear correlation between the patients` disability measured by Expanded Disability Status Scale score and Cu and Mg, while a negative linear correlation between Zn and Zn/Cu ratio. Conclusion: There is a disturbed oxidative status in MS patients shown by the higher increment of Cu and decrement of Zn, Mg and Zn/Cu ratio in MS patients, in addition to their relation with patients` disability than the control group, making it easy to quantify and predict MS disability objectively.